Pesticides residues determination and probabilistic health risk assessment in the soil and cantaloupe by Monte Carlo simulation: A case study in Kashan and Aran-Bidgol, Iran - Mohsen Hesami Arani; Majid Kermani; Roshanak Rezaei Kalantary; Neamatollah Jaafarzadeh; Samaneh Bagheri Arani (Ecotoxicology and Environmental Safety, 2023)
Cantaloupe is a popular agricultural product in the hot season of Iran. On the other hand, the frequent use of pesticides in cantaloupe fields is the most important threat to the health of farmers and consumers. Therefore, the present study aims to measure the concentration of diazinon (DZN), chlorpyrifos (CPF), and malathion (MLT) in cantaloupe cultivated in Kashan and Aran-Bidgol (Iran) and to estimate the possible oral and dermal risk of these pesticides by Monte Carlo simulation (MCS). 36 cantaloupe samples, 18 samples before, and 18 samples after the latent period were collected from different places of cantaloupe cultivation from April to May 2021. After measuring the pesticides using the QuEChERS approach, oral and dermal risk assessments were calculated.The mean and standard deviation of the concentrations of chlorpyrifos, malathion, and diazinon in 18 cantaloupe samples, after the latent period, were (30.39 ± 13.85), (18.361 ± 1.8), and (21.97 ± 0.86) μg kg-1, respectively. Concentration of Malathion, diazinon, and Chlorpyrifos in the soil were 0.22, 0.25, and 0.3 mg kg-1, respectively, and pesticide cumulative risk assessment in soil was obtained 0.011 for Malathion, 0.05 for diazinon and 0.03 for Chlorpyrifos. Target Hazard Quotient (THQ) according to the cantaloupe consumption and dermal exposure in children and adults, was safe range. Although non-cancerous dermal and oral risk of cantaloupe is low, constant exposure can be harmful. Therefore, the findings of this study play an important role in increasing the understanding of the negative health consequences of pesticide contamination in cantaloupe for consumers, especially local residents, and can help by adopting remedial strategies to reduce environmental concerns.